2011
DOI: 10.1111/j.1460-9568.2011.07951.x
|View full text |Cite
|
Sign up to set email alerts
|

Right–left asymmetry in the cortical processing of sounds for social communication vs. navigation in mustached bats

Jagmeet S. Kanwal

Abstract: In the Doppler-shifted constant frequency processing area in the primary auditory cortex of mustached bats, Pteronotus parnellii, neurons respond to both social calls and to echolocation signals. This multifunctional nature of cortical neurons creates a paradox for simultaneous processing of two behaviorally distinct categories of sound. To test the possibility of a stimulus-specific hemispheric bias, single-unit responses were obtained to both types of sounds, calls and pulse-echo tone pairs, from the right a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 90 publications
4
23
0
Order By: Relevance
“…Since projections to the midbrain arise primarily from the contralateral auditory periphery, the results obtained here support the hypothesis that right-ear/left-hemispheric superiority for processing communication sounds in frogs is to a significant extent due to structural asymmetries in the way the auditory system processes information. This finding is also in agreement with earlier studies on REA in amniote vertebrates holding a left-hemisphere priority for processing conspecific/neighbor vocalizations [1,[16][17][18][19]24,[52][53][54][55][56][57]. Furthermore, the REA in music frogs has been demonstrated, at least in part, in a preliminary behavioral study using a head orienting task in which the subjects preferentially turned their bodies toward the right while listening to HSA playbacks, but did not show a turning preference in silence (unpublished data).…”
Section: Rea As a Mechanism For Processing Acoustic Stimulisupporting
confidence: 91%
See 2 more Smart Citations
“…Since projections to the midbrain arise primarily from the contralateral auditory periphery, the results obtained here support the hypothesis that right-ear/left-hemispheric superiority for processing communication sounds in frogs is to a significant extent due to structural asymmetries in the way the auditory system processes information. This finding is also in agreement with earlier studies on REA in amniote vertebrates holding a left-hemisphere priority for processing conspecific/neighbor vocalizations [1,[16][17][18][19]24,[52][53][54][55][56][57]. Furthermore, the REA in music frogs has been demonstrated, at least in part, in a preliminary behavioral study using a head orienting task in which the subjects preferentially turned their bodies toward the right while listening to HSA playbacks, but did not show a turning preference in silence (unpublished data).…”
Section: Rea As a Mechanism For Processing Acoustic Stimulisupporting
confidence: 91%
“…For non-human animals, left-hemispheric dominance for conspecific communication sounds has been reported in non-human primates [19,[53][54][55]59], other mammals [16,17,24,56,57], birds [60,61] and frogs [10]. Interestingly, communication asymmetry has been reported in bats at the level of single cortical neurons, with left-hemispheric neuronal advantage for processing social calls and right-hemispheric neuronal advantage in processing navigational signals [24]. These findings including the present results suggest a phylogenetically early emergence of vocal communication asymmetries [4].…”
Section: Rea As a Mechanism For Processing Acoustic Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…Using three alcohols and one binary mixture as odourants, we found that odour processing is asymmetric: the neural odour representations were more separated in the right AL, and bees with only their right antenna in use were better in segregating a target odour from a background odour in a cross-adaptation experiment. Similarly, in vertebrates the discriminatory power of sensory representations can be lateralized, as has been shown in the visual system of birds [27][28][29][30][31] both behaviourally and physiologically (fMRI during a discrimination task described in [31], electrophysiological recordings in the primary auditory area in [30] and in the auditory system of bats [32]; the latter was revealed by measuring inter-stimuli Euclidean distances).…”
Section: Discussionmentioning
confidence: 99%
“…Lesions of the left hemisphere reduce the ability to discriminate and/or produce conspecific sounds to a greater degree than lesions of the right hemisphere. Neurophysiological studies in bats have shown that the left hemisphere neurons are more responsive to social calls while those of the right are more responsive to navigational signals (Kanwal, 2012). Theoretically, neural lateralization would improve information processing efficiency by providing specialized analysis within each hemisphere, thereby enhancing the ability of land vertebrates to make critical decisions related to mating or feeding in dangerous environments (Rogers et al, 2004).…”
Section: Rea Behaviors Correspond To Known Neural Lateralization Pattmentioning
confidence: 99%